Seleção in silico de sequências de dna espécie-específicas de Leishmania - Oliveira, Fernanda Muller de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Leishmaniasis, a disease caused by the protozoan Leishmania spp. is expanding in the world and affects millions of people annually, reaching 98 countries in tropical and subtropical regions, representing an important public health problem. Subspecies Leishmania and Viannia, represented by at least 22 species, are responsible for the three most common clinical manifestations of the disease in humans. Routinely, in endemic areas, serological diagnosis are employed. However, other parasitological and/or molecular techniques have high sensitivity to identify the genus Leishmania. The publication of Leishmania genomes have provided a better understanding of their composition and molecular markers to identify protozoan species and intra-specific variations, however some species are still underdiagnosed. However, the differentiation of Leishmania species in clinical samples still has limitations. Thus, in order to find the solution for this issue, we sought to design specific sequences for different species of Leishmania deposited in trypanosomatid genomic database, carrying out an in silico assay for verification of the selected sequences. The information generated in this study will constitute an interesting diagnostic platform, after proper validation with clinical samples
Keywords: Leishmaniose; Genoma; DNA; Oligonucleotídeos; Diagnóstico; Primers